Homologous Recombination Repair Defect May Predict Treatment Response to Peptide Receptor Radionuclide Therapy for Neuroendocrine Tumors. (1st July 2020) - Zhu, Mojun; Sonbol, Mohamad Bassam; Halfdanarson, Thorvardur; Hobday, Timothy; Ahn, Daniel; Ma, Wen Wee; Bekaii‐Saab, Tanios
Abstract: : Lutetium‐177‐dotatate ( 177 Lu‐dotatate), a form of peptide receptor radionuclide therapy, was approved by the U.S. Food and Drug Administration for the treatment of advanced somatostatin receptor–positive gastroenteropancreatic neuroendocrine tumors (NETs) in 2018 based on the promising results of the NETTER‐1 trial for grade 1–2 midgut NETs. Here, we present a patient with a grade 3 pancreatic neuroendocrine tumor and BRCA1 germline mutation who had a significant response to 177 Lu‐dotatate. Abstract : This article describes a patient with high‐grade pancreatic neuroendocrine tumor and BRCA1 germline mutation who had a significant response to Lutetium‐177‐Dotatate and summarizes the current state of clinical management of high‐grade neuroendocrine tumors.